(untitled) - Bennis, Warren (New York, 1993)
Warren Bennis is a prolific writer on leadership, having penned Leaders and On Becoming a Leader amongst other books. In this books, he turns inward reflecting on the lessons involved in analyzing his own life. He willingly covers the negative experiences in his life, including an experience where he offered a partial resignation in protest of administrative policy.
Keywords: Leadership,Organizational change,Business ethics